The effect of transglutaminase on gluten-free soy bread baked using ohmic heating. Issue 1 (November 2021) - Hutasoit, J P; Sutrisno, Aji; Murtini, E S; Lastriyanto, A
Abstract: This study aims to compare the quality of gluten-free bread made from black soybean flour using and without transglutaminase (TGase) baked using ohmic heating technology. Parameters of bread quality observed were specific volume, moisture content, texture profile analysis, porosity, and color. To understand the changes in the ohmic heating process parameters during baking, an evaluation of temperature, electrical conductivity, current intensity, electrical power parameters was carried out. To analyze the data, the independent sample t-test method was used. The results obtained indicate that the addition of TGase affects the characteristics of the bread and process parameters during baking with ohmic heating. Bread with the addition of TGase has an increase in volume, texture, moisture content, and porosity of the bread that is better than without the addition of TGase. Based on the parameter process, the rate of increase in temperature, electrical conductivity, current, and power intensity is highly affected by the addition TGase. Electrical conductivity increases linearly with increasing temperature.